Efektifitas Senam Kusta Terhadap Kekuatan Otot Tangan Dan Kaki Penderita Kusta Di UPTD Kesehatan Puskesmas Grati Pasuruan - Etik Mufdilah (MEDICA MAJAPAHIT, 2013)
Most problems occur due to disability in leprosy leprosy disease that attacks the peripheral nerves. Among motor paralysis will affect the strength of the muscles of the hands and feet. Therefore, if the exercise is impaired body movement is essential to increase muscle strength lepers. Gymnastics leprosy is a motor motion exercises that aim to improve muscle function lepers. This study aims to determine the effectiveness of exercise on muscle strength leprosy hands and feet in leprosy patients at the health center Grati Pasuruan UPTD Health. This study uses experimental design that involves Quasy-control group with non-equivalent time sampling approach to design, using a purposive sampling method for sample collection. Respondents who were the subjects of research were 10 people with disabilities lepers level 1. The research was conducted on July 26-August 9, 2011 for 2 weeks. Data collection tool is to check the muscle strength of the hands and feet are then entered on the observation sheet. Statistical tests used were Wilcoxon signed ranks test. The results showed that exercise is effective against leprosy muscle strength in hands and feet of lepers in the health center Grati Pasuruan UPTD Health (P = 0.025 <Î± = 0.05). Gymnastics leprosy is a body movement that focuses on the most important if the motion of the motor nerves in patients with leprosy, so exercise is effective for improving muscle strength and hand kakipenderita leprosy. If the exercise routine every day and is supported by self-care on disability then it is for prevention of disability is more severe in patients with leprosy.